International service learning in the Dominican Republic: An asynchronous pilot in interprofessional education. Issue 2 (3rd March 2016) - Foster, Jennifer; Pullen, Sara
ABSTRACT: Despite the logistical barriers of asynchronous academic calendars, university students in nursing and physical therapy in one academic health centre piloted an international, interprofessional, service learning project in the Dominican Republic. Although the nursing students and physical therapy students were not able to be in-country at the same time, they provided care to a common caseload of traumatic injury patients and those with chronic, debilitating conditions. Interprofessional communication occurred with the development of SBAR (Situation, Background, Assessment, Recommendation) reports from the Team Training curriculum of the Agency for Healthcare Research and Quality. Students learned the depth of physical therapy and the breadth of nursing. The pilot led to a more refined design to pair nursing and PT students, requiring them to communicate via mobile phone regarding results of examinations, and suggestions for follow-up by the nursing students, to ensure continuity of care and a more comprehensive approach to services.